2021
DOI: 10.21315/eimj2021.13.4.9
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of e-Mentoring Medical Students During the COVID-19 Pandemic

Abstract: In the current pandemic scenario, the School of Medical Sciences, Universiti Sains Malaysia had adopted an e-mentoring system to help undergraduate medical students acclimatise to new subjects, improve academic performance and decrease attrition. The authors highlight the challenges of e-mentoring, including aspects of interpersonal dynamics, slow development of relationships in e-mentoring and the requirement of specific skills in technology for useful online mentoring, are the few challenges discussed. Some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Simok et al [ 41 ] addressed the challenges of online learning, stating that appropriate preparation, training, and preventive measures, were among them. They suggested that future research on e-mentoring platforms or modules to optimize their efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Simok et al [ 41 ] addressed the challenges of online learning, stating that appropriate preparation, training, and preventive measures, were among them. They suggested that future research on e-mentoring platforms or modules to optimize their efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have highlighted the well-being and needs of each party but have not yet looked at the interactions between students, teachers, and the environment/systems, although social connectedness is found to be one of the key factors affecting students’ well-being [ 12 ]. Simok et al (2021) argued that online interaction might hinder relationship building between students and teachers, some of which are caused by the speed and amount of information exchanged online [ 13 ]. Furthermore, these interactions might also be difficult to be monitored remotely [ 3–5 ].…”
Section: Introductionmentioning
confidence: 99%